(untitled) (Bangladesh Journal of Medical Science, 2023)
Objective: Infertile couples experienced a tremendous amount of emotional turmoil as the result of their diagnosis and have struggled to conceive, leading to an increased risk of anxiety and depression. In Vietnam, few authors mention anxiety and depression in couples undergoing infertility treatment, especially in rural areas where the qualification and technology in infertility treatment is limited than specialized hospitals in big cities. This study was conducted to determine the prevalence of anxiety and depression in couples undergoing infertility treatment and some related factors. Materials and methods: The descriptive cross-sectional study was carried out from November 2020 to May 2021. The study subjects included 385 couples (385 wives and 385 husbands) who came for infertility examination and treatment at the Department of Reproductive Health Care, Center for Disease Control (CDC) of KienGiang Province. The Vietnamese version of the DASS 21 scale was used to measure anxiety and depression through face-to-face interviews with a structured set of questions. Participants were also asked about demographics, socioeconomic status, infertility-related characteristics, and family relationships. Results and Discussion: The prevalence of anxiety among wives is higher than that of husbands (46.2% and 33.3%), similarly the prevalence of depression among wives (17.7%) is also higher than that of husbands (10.06%). Most couples have mild or moderate anxiety disorders, the same goes for depression. In husbands, there is a factor related to anxiety that is living separately (i.e. the couple does not live with their parents in the same house) and there are 2 factors related to depression which are living separately and family economic conditions. Among the wives, more factors were found to be associated with anxiety and depression, including age, living separately, family economic conditions and duration of infertility. Conclusion: The prevalence of anxiety and depression among infertile couples in the rural province of the South, Vietnam is high. Although most anxiety and depression levels are mild or moderate, emotional and mental support must be integrated with clinical support is really necessary, helping to improve the patient’s quality of life and indirectly improve the effectiveness of infertility treatment. Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 360-367